Quality Management Audit: Problems, Decisions, and Perspectives - Elena Khunuzidi; Vladimir Shper; Vladimir Smelov (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
This study addresses the pervasive issue of distrust in audit results, a concern frequently observed in professional practice and corroborated by existing literature. The immediate objective of this research is to identify the underlying causes of this distrust and to propose practical solutions. Ultimately, our goal is to foster an environment where stakeholders can make informed management decisions based on objective and reliable audit outcomes. The methodology employed in this study integrates systems thinking, statistical analysis, and Deming's theory of profound knowledge, utilizing various tools of statistical process control. Our findings indicate that the primary cause of distrust in audit results is the imprecise formulation of requirements for audited entities. Additionally, auditors typically lack accountability for poor-quality work despite the significant potential consequences of their errors for organizations and stakeholders. We propose the implementation of a novel evidence-based audit approach aimed at enhancing the credibility of audits and, consequently, the quality of management decisions derived from them. The cornerstone of this new procedure is the Shewhart control chart, which serves as the primary tool for ensuring the reliability and objectivity of audit results.
Keywords: M10; 330; evidence-based audit; management decisions; profound knowledge; Deming; Shewhart control charts; quality management systems